Transformation in the Javakheti Highlands Georgia – a Community-based Participatory Approach Towards Sustainable Pasture Management in a Remote Mountain Area - Susanne Elsen; Stefan Zerbe (Проблеми на постмодерността, 2018)
In many regions of the world, societies are in a phase of rapid transition due to political and socio-economic changes, combined with changes in the natural environment, climate change and biodiversity loss. In the case study presented here, we address the Armenian population of the remote rural area of the Javakheti Highlands in the South Caucasus of Georgia, situated next to the Turkish frontier. Actors in this region have to deal with cumulative uncertainties related to the complex processes of post-Soviet transition and its social, cultural and economic consequences. Any transformative intention that effects local population has to be embedded into everyday life context. Entering in such an unclear situation as western researchers with the mission to generate possible answers to a vital economic and socio-cultural question, asks for comprehensive approaches following primarily the needs of the local people, integrating different perspectives of scientists, stakeholders and concerned population.